2018
DOI: 10.12659/pjr.899609
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary Ultrasonographic Abnormalities in Adult Patients with Sickle Cell Anaemia in Steady State in Ile-Ife, Nigeria

Abstract: SummaryBackgroundSickle cell anaemia (SCA) is associated with structural manifestations in the hepatobiliary axis. This study aimed to investigate the hepatobiliary ultrasonographic abnormalities in adult patients with sickle cell anaemia in steady state attending the Haematology clinic of a federal tertiary health institution in Ile-Ife, Nigeria.Material/MethodsBasic demographic data as well as right upper abdominal quadrant ultrasonography of 50 consecutive sickle cell anaemia patients were compared with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…However, in our study, we clearly noted the limitations of our findings that “findings were not specific, as no biopsy or any other imaging modality was used to confirm sonographic findings. [1] Previous studies[23] reported similar findings.…”
supporting
confidence: 61%
“…However, in our study, we clearly noted the limitations of our findings that “findings were not specific, as no biopsy or any other imaging modality was used to confirm sonographic findings. [1] Previous studies[23] reported similar findings.…”
supporting
confidence: 61%
“…The results showed that a quarter of participants developed cholelithiasis at a mean age of 6.9 years. However, previous studies have reported prevalence of cholelithiasis in the range if 4.2%–58% 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21. This wide range in cholelithiasis frequency is mainly attributable to differences in geographic area and age group as well as differing inclusion and exclusion criteria among studies.…”
Section: Discussionmentioning
confidence: 96%
“…[ 6 ] A study conducted by Oguntoye et al . [ 7 ] on hepatobiliary ultrasonographic abnormalities in adult patients with SCA in steady state in Ile-Ife, Nigeria, among 50 SCA and 50 age- and sex-matched subjects with HbAA as controls. The result shows that among the patients, 32 (64%) had hepatomegaly, 15 (30%) cholelithiasis, and 3 (6%) biliary sludge.…”
Section: Introductionmentioning
confidence: 99%